2002
DOI: 10.1002/hyp.1077
|View full text |Cite
|
Sign up to set email alerts
|

Winter chemical leaching from deciduous tree branches as a function of branch inclination angle in central Massachusetts

Abstract: Abstract:Leaching is an important process in the biogeochemical cycling of nutrients from above-ground vegetative surfaces to the forest floor. Little is known about winter leaching from deciduous tree species and the influence of branch inclination angle on leachate chemistry. Using a set of field-based isolated branches harvested from mature crowns of Betula lenta, Carya glabra and Quercus rubra, we tested the null hypothesis that during winter neither branch inclination angle nor branch species would have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 27 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…6). These results match those observed in earlier studies (Inagaki et al 1995;Levia and Herwitz 2002), in which DOC concentrations in stemflow were regulated by retention time when precipitation was retained in bark, which implies that the DOC concentration in the stemflow is affected by different bark morphologies. DOC concentration was higher in Quercus stemflow than in Betula stemflow, owing to the rough and multilayered fibrous bark of Quercus, which thus retains precipitation longer than the single-layered bark of Betula does allowing more DOC to leach.…”
Section: Variations and Regulation Of Doc Concentrationsupporting
confidence: 91%
“…6). These results match those observed in earlier studies (Inagaki et al 1995;Levia and Herwitz 2002), in which DOC concentrations in stemflow were regulated by retention time when precipitation was retained in bark, which implies that the DOC concentration in the stemflow is affected by different bark morphologies. DOC concentration was higher in Quercus stemflow than in Betula stemflow, owing to the rough and multilayered fibrous bark of Quercus, which thus retains precipitation longer than the single-layered bark of Betula does allowing more DOC to leach.…”
Section: Variations and Regulation Of Doc Concentrationsupporting
confidence: 91%
“…Remarkably little work has been accomplished hitherto on the interrelationships between canopy structure and stemflow chemistry. Levia and Herwitz [] found that branch inclination angle did, in fact, have a detectable effect on stemflow leachate chemistry. Branches inclined at 20° above the horizontal had significantly higher base cation fluxes in branchflow than branches inclined at 5° or 38° [ Levia and Herwitz , ].…”
Section: Stemflow Yield and Chemistry In Relation To Canopy Structurementioning
confidence: 99%
“…Levia and Herwitz [] found that branch inclination angle did, in fact, have a detectable effect on stemflow leachate chemistry. Branches inclined at 20° above the horizontal had significantly higher base cation fluxes in branchflow than branches inclined at 5° or 38° [ Levia and Herwitz , ]. It was concluded that the 20° branch achieved the optimal balance between drop capture and branchflow volume and a long enough residence time of the intercepted precipitation on the branch surface to increase leachate concentrations and fluxes.…”
Section: Stemflow Yield and Chemistry In Relation To Canopy Structurementioning
confidence: 99%
“…In contrast, stemflow has been observed to be larger for deciduous trees in the leafless canopy state (Helvey and Patric, 1965;Levia and Frost, 2003;Staelens et al, 2011), suggesting that the exposure of a tree's woody frame promotes stemflow production. Levia and Herwitz (2002) further linked branch angle with branch flow solute chemistry. Advancing the findings of earlier work, the primary objective of our research is to provide a novel understanding of stemflow generation processes in relation to canopy structure by identifying the individual canopy structural metrics that exert the greatest influence on stemflow production from European beech (Fagus sylvatica L.).…”
Section: Introductionmentioning
confidence: 99%